Hypertrophic Cardiomyopathy in the Elderly: A Case Identified With Genetic Screening - Gaspar Del Rio-Pertuz MD; Pooja Sethi MD; Deephak Swaminath MD; Erwin Argueta-Sosa MD (SAGE Publishing, 2022)
Hypertrophic cardiomyopathy (HCM) is a hereditary disease with an autosomal dominant pattern of inheritance, that is caused by a mutation in one of several sarcomere genes that encodes components of the contractile system of the heart. Hypertrophic cardiomyopathy has been described as a disease that is more heavily diagnosed in the second decade of life, that may present with abnormal syncopal episodes or sudden cardiac death. However, with a better understanding of the genetic changes that occur in HCM and with improved imaging techniques, there has now been an increased recognition of a late-onset disease that can occur in the elderly population. We report a case of a 73-year-old woman who was found to have HCM after various clinical events took place.